Foreign Aid and Microfinance: A new policy proposal for financing development - Lacalle-Calderón, Maricruz; Alfonso-Gil, Javier; Rico-Garrido, Silvia (Revista Iberoamericana de Estudios de Desarrollo)
In this paper, we review and compare the potential and limitations of foreign aid and microfinance as a top-down and bottom-up approaches to financing the development process in poor countries. We not only sustain that reviewing foreign aid is a must for the future of the least-developed countries but also posit that microfinance is a complementary and financially sustainable approach that creates better incentives for development. After calculating the potential effects of microfinance over employment and GDP through a simple empirical exercise, we propose a policy recommendation of redirecting a very small share of official development aid (ODA) resources to microfinance in order to provide options for the most underprivileged populations.